Finding Myself Abroad: Adolescent Identity Processes and Sociocultural Adaptation During Intercultural Transitions. (May 2019) - Greischel, Henriette; Noack, Peter; Neyer, Franz J.
The present study examined identity development and sociocultural adaptation (SCA) in the context of international mobility experiences. Specifically, we investigated changes and dynamic interactions of SCA and the Host and Home identity dimensions of commitment and reconsideration for adolescent sojourners. Therefore, we used data from 457 German high school exchange students (72.00% female; M age = 15.49 years, SD = 0.70 years) to study the longitudinal interplay of personality characteristics at two occasions over a period of 5 months. The first wave of data collection (T1) took place 8 weeks after the cultural transition. After 7 months abroad, the second measurement (T2) was taken. Longitudinal analyses revealed increases in Host reconsideration, Home commitment, and SCA, as well as a substantial decrease in Home reconsideration over the course of the study. In addition, initial identity levels predicted changes in SCA, whereas adaptation levels showed no predictive effect on later identity change. Indicators of subjective and objective sociocultural distance were tested as moderators for the effect of identity on changes in adaptation. However, results indicated that the impact identity had on adaptation was independent from influences of cultural distance, which further supported the robustness of identity effect patterns. The present research adds a longitudinal perspective on the association of identity and adaptation and contributes to the understanding of their dynamic interplay during cross-cultural transitions.